Random allocation of blastomere descendants to the trophectoderm and ICM of the bovine blastocyst - Sepulveda-Rincon, Lessly P.; Dube, Delphine; Adenot, Pierre; Laffont, Ludivine; Ruffini, Sylvie; Gall, Laurence; Campbell, Bruce K.; Duranthon, Veronique; Beaujean, Nathalie; Maalouf, Walid E. (Society for the Study of Reproduction, 2016)
The first lineage specification during mammalian embryo development can be visually distinguished at the blastocyst stage. Two cell lineages are observed on the embryonic-abembryonic axis of the blastocyst: the inner cell mass and the trophectoderm. The timing and mechanisms driving this process are still not fully understood. In mouse embryos, cells seem prepatterned to become certain cell lineage because the first cleavage plane has been related with further embryonic-abembryonic axis at the blastocyst stage. Nevertheless, this possibility has been very debatable. Our objective was to determine whether this would be the case in another mammalian species, the bovine. To achieve this, cells of in vitro produced bovine embryos were traced from the 2-cell stage to the blastocyst stage. Blastocysts were then classified according to the allocation of the labeled cells in the embryonic and/or abembryonic part of the blastocyst. Surprisingly, we found that there is a significant percentage of the embryos (∼60%) with labeled and nonlabeled cells randomly distributed and intermingled. Using time-lapse microscopy, we have identified the emergence of this random pattern at the third to fourth cell cycle, when cells started to intermingle. Even though no differences were found on morphokinetics among different embryos, these random blastocysts and those with labeled cells separated by the embryonic-abembryonic axis (deviant pattern) are significantly bigger; moreover deviant embryos have a significantly higher number of cells. Interestingly, we observed that daughter cells allocation at the blastocyst stage is not affected by biopsies performed at an earlier stage.